INKORPORASI VITAMIN E PFAD PADA CAMPURAN GALAKTOMANAN KOLANG-KALING (Arenga pinnata) DAN GUM ACASIA - REZA ZULMI; Jamaran Kaban; Juliati Tarigan (JURNAL KIMIA MULAWARMAN, 2018)
Incorporation of vitamin E from palm fatty acid distillate (PFAD) into matrix of mixed gum acacia and galactomannan from Arenga pinnata (kolang-kaling) (GAP) has been studied. Galactomannan extracted from Arenga pinnata was 4.7%. Incorporations were conducted using using 7 gram gum acacia (GA), 1.3 gram vitamin E from PFAD and GAP varied from 0.1 – 0.4 gram in 100 ml total volume. The thickness of the film occurred in the range of 0.600 – 0.780 mm. In the increment of GAP amount the viscosity and stability of film was increased. The best film obtained which most compatible and has viscosity similar with standard of ISO 9001 – 2008 and ISO 22000 – 2005 was from formula 3 contained 0.2 gram GAP. The oncentration of vitamin E determined using gas chromatography was 75.4501%. The composition of vitamin E was tocotrienol 74.41% and tocopherol 25.59%.